On the long-run monetary neutrality : evidence from the SEACEN countries. - Puah, Chin Hong; Habibullah, Muzafar Shah; Abu Mansor, Shazali (EuroJournals, 2008)

(untitled)
This paper tests the long run neutrality (LRN) and long run super neutrality (LRSN) propositions using annual observation from 10 member countries of the South East Asian Central Banks (SEACEN) Research and Training Centre. The Fisher and Seater (1993) methodology is applied to do the task. Special attention has been given in identifying the number of unit root and cointegrating vector, as a meaningful LRN (LRSN) test is critically depends on such properties. Empirical results reveal that LRN can be deviated from the case of Asian developing economies. In particular, monetary expansion seems to have long run positive effect on real output in the economies of Indonesia, Taiwan and Thailand. However, LRSN is neither fail or not addressable in our study.